Denaro, natura e separazione. Note sull’uso del concetto di Stoffwechsel dal manoscritto Reflection (1851) ai Grundrisse (1857/58) di Karl Marx - Murrone, Paolo (Bollettino Filosofico, 2025)
Over the past thirty years, the Marxian concept of Stoffwechsel – “metabolism” or “material interchange” – has undergone a radical rediscovery and reinterpretation. Its significance lies in its capacity to dialectically intertwine nature and society within an articulated web of relations, thereby highlighting the materiality of the capitalist mode of production. This paper explores the earliest uses of Stoffwechsel in Marx’s writings, focusing on the manuscript Reflection (1851) and the Grundrisse (1857-58). The historiographical aim is to uncover the deep connection between Marx’s reflections on metabolism and the formation of his critique of political economy. In doing so, the paper seeks to illuminate the semantic breadth of the concept, arguing that it is not only key to understanding the relationship between capital and nature but also a social and political category that captures the reproductive logic of capitalist society and its forms of impersonal domination. Keywords: Marx, Nature, Money, Separation, Stoffwechsel